2009
DOI: 10.1002/adfm.200900105
|View full text |Cite
|
Sign up to set email alerts
|

Beam to String Transition of Vibrating Carbon Nanotubes Under Axial Tension

Abstract: State‐of‐the‐art nanoelectromechanical systems have been demonstrated in recent years using carbon nanotube (CNT) based devices, where the vibration of CNTs is tuned by tension induced through external electrical fields. However, the vibration properties of CNTs under axial tension have not been quantitatively determined in experiments. Here, a novel in situ method for precise and simultaneous measurement of the resonance frequency, the axial tension applied to individual CNTs and the tube geometry is demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…They were fabricated by a chemical vapor deposition (CVD) technique on Si substrates 33. Their structural, electrical, and mechanical thermoelectric properties have been reported elsewhere 34. Bundles of the MWCNTs tubes were mechanically cut from the original substrates, then one or several pieces of the bundles with the same diameter, ranging from 65 to 230 µm (Table 1), were mounted onto a testing device made from a piece of commercial coaxial copper cable (RG174).…”
Section: Methodsmentioning
confidence: 99%
“…They were fabricated by a chemical vapor deposition (CVD) technique on Si substrates 33. Their structural, electrical, and mechanical thermoelectric properties have been reported elsewhere 34. Bundles of the MWCNTs tubes were mechanically cut from the original substrates, then one or several pieces of the bundles with the same diameter, ranging from 65 to 230 µm (Table 1), were mounted onto a testing device made from a piece of commercial coaxial copper cable (RG174).…”
Section: Methodsmentioning
confidence: 99%
“…(2) is the nth eigenfrequency of a string. Wei et al [39] observed that when T L 2 /EI > 2000, a carbon nanotube vibrates as a string rather than a beam; Unterreithmeier et al [40] also found that when σ > 100 MPa, the stretching energy of a silicon nitride nanowire is dominant and the bending energy becomes negligible, which means the string behavior dominates. Many one-dimensional mechanical resonators are modeled as a string because of the presence of large tension [3, A c c e p t e d M a n u s c r i p t 4,8,25].…”
Section: Introductionmentioning
confidence: 95%
“…In this paper, we extend our previous works [ 10 , 16 , 17 ] to report the modified technique capable of mass determination in viscous fluid without the necessity of knowing the surrounding fluid density and viscosity. This technique utilizes the measurement of the fundamental resonant frequencies of the micro-/nanomechanical mass sensor under different values of the intentionally applied axial tensile force, which is created and controlled either via an external electrical/electromagnetic field [ 5 , 17 ] or mechanically [ 18 ]. In addition, due to the importance in real application use, we show that the commonly achievable force measurement errors, e.g., inaccuracy in the estimation of the electrical force, have a negligibly small impact on the extracted mass values.…”
Section: Introductionmentioning
confidence: 99%